FACTORS INFLUENCING DAM SURVIVAL RATE IN BOVINES SUBJECTED TO CAESAREAN-SECTION
Forty-one dystocia affected bovines subjected to caesarean were assessed to investigate the influence of various factors on dam survival rate. With reference to type of suture material (chromic catgut, CC or polyglycolic acid, PGA) used for closing uterine incision either with or without infusion ofan intra-peritoneal lubricant (sodium carboxy methyl cellulose, SCMC, 1 % @ 14 ml/kg), the animals were divided into group la (PGA+SCMC